Cloning and characterization of Rrp1, the gene encoding Drosophila strand transferase: carboxy-terminal homology to DNA repair endo/exonucleases. - Sander, M (1991)
We previously reported the purification of a protein from Drosophila embryo extracts that carries out the strand transfer step in homologous recombination (Lowenhaupt, K., Sander, M., Hauser, C. and A. Rich, 1989, J. Biol. Chem. 264, 20568). We report here the isolation of the gene encoding this protein. Partial amino acid sequence from a tryptic digest of gel purified strand transfer protein was used to design a pair of degenerate oligonucleotide primers which amplified a 635 bp region of Drosophila genomic DNA. Recombinant bacteriophage were isolated from genomic and embryo cDNA libraries by screening with the amplified DNA fragment. These bacteriophage clones identify a single copy gene that expresses a single mRNA transcript in early embryos and in embryo-derived tissue culture cells. The cDNA nucleotide sequence contains an open reading frame of 679 amino acids within which are found 5 tryptic peptides from the strand transfer protein. Expression of this cDNA in E. coli produces a polypeptide with the same electrophoretic mobility as the purified protein. The deduced protein sequence has two distinct regions. The first 427 residues are basic, rich in glutamic acid and lysine residues and unrelated to known proteins. The carboxy-terminal 252 residues are average in amino acid composition and are homologous to the DNA repair proteins, Escherichia coli exonuclease III and Streptococcus pneumoniae exonuclease A. This protein, which we name Rrp1 (Recombination Repair Protein 1), may facilitate recombinational repair of DNA damage.